The Intuitive Law Idea in the Concept of L. Petrazhytsky - Атоян, Ольга Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The issue of intuitive law theory as ingredient of the concept of L. Petrazhitsky's psychological school of jurisprudenceis researched in this article.